Oxalic acid excretion after intravenous ascorbic acid administration - Robitaille, Line (2009)
Ascorbic acid is frequently administered intravenously by alternative health practitioners and, occasionally, by mainstream physicians. Intravenous administration can greatly increase the amount of ascorbic acid that reaches the circulation, potentially increasing the risk of oxalate crystallization in the urinary space. To investigate this possibility, we developed gas chromatography mass spectrometry methodology and sampling and storage procedures for oxalic acid analysis without interference from ascorbic acid and measured urinary oxalic acid excretion in people administered intravenous ascorbic acid in doses ranging from 0.2 to 1.5 g/kg body weight. In vitro oxidation of ascorbic acid to oxalic acid did not occur when urine samples were brought immediately to pH less than 2 and stored at –30°C within 6 hours. Even very high ascorbic acid concentrations did not interfere with the analysis when oxalic acid extraction was carried out at pH 1. As measured during and over the 6 hours after ascorbic acid infusions, urinary oxalic acid excretion increased with increasing doses, reaching approximately 80 mg at a dose of approximately 100 g. We conclude that, when studied using correct procedures for sample handling, storage, and analysis, less than 0.5% of a very large intravenous dose of ascorbic acid is recovered as urinary oxalic acid in people with normal renal function.